Impact of exogenous rhamnolipids on plant photosynthesis and biochemical parameters under prolonged heat stress - M.A. BOUCHRATI; S. VILLAUME; J.F. GUISE; I. FEUSSNER; N. VAILLANT-GAVEAU; S. DHONDT-CORDELIER (Photosynthetica)
High temperatures severely affect plant growth and development leading to major yield losses. These temperatures are expected to increase further due to global warming, with longer and more frequent heat waves. Rhamnolipids (RLs) are known to protect several plants against various pathogens. To date, how RLs act under abiotic stresses is unexplored. In this study, we aimed to investigate whether RLs could modify Arabidopsis thaliana physiology during prolonged heat stress. Measurement of leaf gas exchange and chlorophyll fluorescence showed that heat stress reduces photosynthetic rate through stomatal limitation and reduction of photosystem II yield. Our study reported decreased chlorophyll content and accumulation of soluble sugars and proline in response to heat stress. RLs were shown to have no detrimental effect on photosynthesis and carbohydrate metabolism in all conditions. These results extend the knowledge of plant responses to prolonged heat stress.